Prestimulus amplitudes modulate P1 latencies and evoked traveling alpha waves - Himmelstoss, Nicole A.; Brötzner, Christina P.; Zauner, Andrea; Kerschbaum, Hubert H.; Gruber, Walter; Lechinger, Julia; Klimesch, Wolfgang (Frontiers in Human Neuroscience, 2015)
Traveling waves have been well documented in the ongoing, and more recently also in the evoked EEG. In the present study we investigate what kind of physiological process might be responsible for inducing an evoked traveling wave. We used a semantic judgment task which already proved useful to study evoked traveling alpha waves that coincide with the appearance of the P1 component. We found that the P1 latency of the leading electrode is significantly correlated with prestimulus amplitude size and that this event is associated with a transient change in alpha frequency. We assume that cortical background excitability, as reflected by an increase in prestimulus amplitude, is responsible for the observed change in alpha frequency and the initiation of an evoked traveling trajectory.